Ecce Homo : A Survey of the Life and work of Jesus Christ - Seeley, J.R 1974- (London : Macmillan and Co. Limited, 1916)
Interacting with theologians throughout the ages, Riches narrates the development of the churchs doctrine of Christ as an increasingly profound realization that the depth of the difference between the human being and God is realized, in fact, only in the perfect union of divinity and humanity in the one Christ. He sets the apostolic proclamation in its historical, theological, philosophical, and mystical context, showing that, as the starting point of {28}orthodoxy
Part I. The unity of Christ : -- 1. Against separation -- 2. The humanity of Christ -- 3. Chalcedonian orthodoxy -- Part II. The synergy of Christ : -- 4. Mingling and inversion -- 5. Theopaschism -- 6 Dyothelite unity -- Part III. The existence of Christ : -- 7. The divine esse -- 8. Theandric action -- 9. Union and abandon -- 10. Son of Mary -- Coda : The communion of Jesus and Mary : -- 11. The weight of the cross.
Includes bibliographical references (pages 250-272) and index.
Keywords: Jesus Christ -- Natures; Jesus Christ